L’attualità della cartografia storica fra convergenze disciplinari e nuove tecnologie - Dai Prà , Elena (GEOmedia, 2010)
Historical cartography between disciplinary convergence and new technologies. This paper aims to present a research project lead by Trento University, the so called APSAT-Ambiente e Paesaggi dei Siti d'Altura Trentini, in wich is involved a geo-historical research unit. Its main subject is to carry out methodological exempla on historical maps analysis, in order to investigate historical and cultural landscape, but in particular about planning, e.g. for water management, protected areas, border landscape, historical topography/ toponimy analysis.